2019
DOI: 10.3389/fbioe.2019.00261
|View full text |Cite
|
Sign up to set email alerts
|

Hazard Assessment of Polymeric Nanobiomaterials for Drug Delivery: What Can We Learn From Literature So Far

Abstract: The physicochemical properties of nanobiomaterials, such as their small size and high surface area ratio, make them attractive, novel drug-carriers, with increased cellular interaction and increased permeation through several biological barriers. However, these same properties hinder any extrapolation of knowledge from the toxicity of their raw material. Though, as suggested by the Safe-by-Design (SbD) concept, the hazard assessment should be the starting point for the formulation development. This may enable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 127 publications
0
46
0
2
Order By: Relevance
“…In fact, all authors mentioned used similar DDA Chit (75-85%) and no pattern could be observed. Moreover, those results are also affected by other variables, such as the different cellular models and testing conditions, namely concentrations, used by each author, as previously reviewed elsewhere (Jesus et al, 2019). Furthermore, none of the studies mentioned used RAW 264.7 cells, which hinders the comparison with the results herein presented.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In fact, all authors mentioned used similar DDA Chit (75-85%) and no pattern could be observed. Moreover, those results are also affected by other variables, such as the different cellular models and testing conditions, namely concentrations, used by each author, as previously reviewed elsewhere (Jesus et al, 2019). Furthermore, none of the studies mentioned used RAW 264.7 cells, which hinders the comparison with the results herein presented.…”
Section: Discussionmentioning
confidence: 87%
“…These contradictions and ambiguity may be due to differences in the used Chit polymers or in vitro methodology, namely the cellular model, NP concentration and incubation period. Moreover, it has been observed that most of the studies do not properly characterize, or at least do not report, both the polymer and the derived NPs, nor use or report adequate controls to screen NP interferences or monitor the presence of endotoxin contamination (Jesus et al, 2019). Notably, in the context of Safe-by-Design (SbD) of new polymeric NPs for drug delivery, it is necessary to rely on assertive results of immunotoxicity and hemocompatibility, obtained with properly characterized polymeric NPs.…”
Section: Introductionmentioning
confidence: 99%
“…This may be a result of the lack of standardized assays, which lead to a high variation in reported studies (Hofmann-Amtenbrink et al, 2015). Also some studies have no proper characterization and lack appropriate controls specific to the nanoscale (Jesus et al, 2019), which makes comparisons between toxicity outcomes difficult. Therefore, experimental studies are still needed.…”
Section: Gonanobiomat Sbd Approachmentioning
confidence: 99%
“…In fact, the superiority of nanosystems has been demonstrated in certain applications of the respiratory field, as will be described in the following sections of the review. The nanocarriers permit drug protection, provide a greater ability to interact with the tissues and cells, owing to the high surface area, often allowing specific targeting and/or controlled drug release [38]. However, the proposal of nanocarriers must not be blind, and it is important to note that some applications may take greater benefit from the use of microcarriers, for example if the therapeutic target is phagocytic cells such as macrophages.…”
Section: Introductionmentioning
confidence: 99%